THE HYBRID SPOT WELDING – EPOXY BONDING PROCESS FOR AISI 1008 STEEL: THE EFFECT OF EPOXY ADHESIVE TYPE - Paryanto Dwi Setyawan; I W. Ogie Sabaniartha; Andi Maulana; Sugiman; Sujita; Suteja (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2026)
Hybrid joining technologies are increasingly being explored to overcome the mechanical and durability limitations associated with conventional resistance spot welding (RSW) and adhesive bonding in lightweight steel structures. However, despite the growing interest in spot welding–epoxy bonding (SWEB), the combined influence of adhesive curing behavior and welding thermal input on joint integrity and microstructural evolution remains insufficiently understood. In this work, a comprehensive experimental study was conducted on 0.8 mm AISI 1008 steel sheets joined using three commercial epoxy systems with different curing characteristics, combined with varying welding currents (50–80 A) and welding times (10–20 s). The investigation integrated mechanical shear testing with metallographic and compositional analyses to establish direct correlations between process parameters, microstructural transformations, and failure behavior. The findings reveal that the hybrid joints exhibit a synergistic load-transfer mechanism capable of significantly improving joint strength and energy absorption compared with conventional spot welds. Superior performance was consistently obtained using slow-curing epoxy under moderate welding conditions ( 60–70 A and 15 s), where a more stable interfacial interaction was achieved. In addition, localized carbon enrichment within the weld nugget, attributed to epoxy pyrolysis during welding, was identified as a previously underexplored phenomenon influencing joint behavior. The study provides new insight into thermo-chemical coupling in SWEB systems and proposes a practical pathway for tailoring hybrid joining performance through integrated process design.